Metastatic pulmonary carcinomas in cats (‘feline lung–digit syndrome’): further variations on a theme - Thrift, Elizabeth (JFMS Open Rep, 2017)
CASE SERIES SUMMARY: The aim of this retrospective case series was to describe seven cases where cats with primary lung tumours were presented because of metastases to extra-pulmonary sites (‘feline lung–digit syndrome’). Specifically, we wanted to emphasise less typical case descriptions where tumour emboli resulted in lesions developing in the musculature (including the muscles of the head), skin or distal aorta. RELEVANCE AND NOVEL INFORMATION: The cases are presented to increase clinical awareness of this entity in feline practice, especially when characteristic combinations of clinical signs are present. When clinicians have a high index of suspicion for these presentations, radiology (thorax and digits) or ultrasound (distal aorta), combined with collection of fine needle aspirate specimens for cytology, are usually sufficient to secure a definitive diagnosis. Novel information in this series includes CT and MRI findings from some cases. Typically, needle aspiration or biopsy targeting the skin, digits and lesions in musculature is far easier compared with sampling the primary tumour site in the lungs. The differential diagnosis and investigation of multiple digital lesions is also considered.